2017
DOI: 10.1038/srep40701
|View full text |Cite
|
Sign up to set email alerts
|

Oriented and Ordered Biomimetic Remineralization of the Surface of Demineralized Dental Enamel Using HAP@ACP Nanoparticles Guided by Glycine

Abstract: Achieving oriented and ordered remineralization on the surface of demineralized dental enamel, thereby restoring the satisfactory mechanical properties approaching those of sound enamel, is still a challenge for dentists. To mimic the natural biomineralization approach for enamel remineralization, the biological process of enamel development proteins, such as amelogenin, was simulated in this study. In this work, carboxymethyl chitosan (CMC) conjugated with alendronate (ALN) was applied to stabilize amorphous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
87
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 61 publications
2
87
0
2
Order By: Relevance
“…29 The proteins probably acted as a scaffold for ion exchange of NHA and CP. 22,31 These results relate to the capabilities of NHA gel and CP to perform the remineralization process. 13 The NHA has a significantly higher capability of remineralization than CP, and this is possibly related to the NHA's nanoparticle nature, which is compatible with tooth structure.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…29 The proteins probably acted as a scaffold for ion exchange of NHA and CP. 22,31 These results relate to the capabilities of NHA gel and CP to perform the remineralization process. 13 The NHA has a significantly higher capability of remineralization than CP, and this is possibly related to the NHA's nanoparticle nature, which is compatible with tooth structure.…”
Section: Discussionmentioning
confidence: 95%
“…29 The protein matrix comprises ~1% of the organic part of a mature enamel, which possibly remains after demineralization and functions as the main scaffold for ionic conduction 30 and deposition in the nanogaps of the interprismatic space, as described by other studies. 30,31 The enamel proteins situated in the interprismatic space were possibly capable of capturing the mineral solutions and allowed for penetration of minerals along the sides of these crystallites. 29,31 This is also related with isomorphic and isoionic exchange processes in enamel crystals that occurred upon the diffusion of calcium and phosphate through the interprismatic spaces and converted into hydroxyapatite crystals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The above technique could be a potential procedure for managing the initial caries in minimal invasive dentistry. 107 Liu et al demonstrated the ability of ferumoxytol to disrupt the intractable oral bio-lms and prevention of tooth decay (dental caries) through intrinsic peroxidase-like activities. Ferumoxytol binds to the bio-lm ultra-structure and produces free radicals from hydrogen peroxide (H 2 O 2 ), which causes in situ bacterial mortality through cell membrane disruptions and degradation of the extra-cellular polymeric substance matrix.…”
Section: Dental Applications Of Nanomaterialsmentioning
confidence: 99%